From the Belly of the Tomb to the Bone: The permanence. Oswaldo Guayasamín - Perea Anda, Mónica (2015)
This paper aims to establish the relationship, Huaca-graybeard-uterus (earth-nature-life-homeland-tender, feminine), bone-(memory -continuity), which appears as a recurring element throughout the work of the Ecuadorian painter Osvaldo Guayasamín, born of his experiential culture-historical and emotionalrelationship with pre-Columbian and hence raises the irreducibility of life, in: While I live, I always remember you. The age of tenderness.